From "Lodz Art" to "Friendly City". Good Practices or New Quality in the Dissemination of Cultural Assets? - Pawłowska, Aneta; Rutkowska-Siuda, Daria; Długosz, Paulina (Protection of Cultural Heritage, 2022)
The Law of July 19, 2019 on Ensuring Accessibility for Persons with Special Needs has opened a new perspective for activities targeting audiences with special needs. On selected grant and project activities conducted by a team of researchers from the University of Lodz and the Museum of the City of Lodz, the possibilities of architectural, information and communication, and digital accessibility will be outlined, which are examples of good practice in the dissemination of cultural assets. Projects related to the revitalization and improvement of the infrastructure of the Museum of the City of Lodz, eliminating architectural barriers and allowing the introduction of a new exhibition space with an information and communication system developed for it, will be presented. The article presents the core concepts related to the "Friendly City" project (implementation in 2021-2024), which precedes the experience gained by the staff of the Lodz University in a series of studies on ways to support people with visual disabilities conducted since 2013. An extremely important area of gathering this experience was the activities undertaken in the project "Lodz art against the background of European art. Excluded/Included." Numerous consultations with groups of people with sensory disabilities, as well as with curators and museum educators, made it possible to develop a well-received form of audiodescription. The didactic tools developed, such as tiffographs, books with Braille and enlarged black print, have significantly increased the competence of key audiences.